2020
DOI: 10.21203/rs.3.rs-63110/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Zierikzee Herbarium: An analysis of the contents and origins of an enigmatic herbarium

Abstract: The Municipal Museum of Zierikzee houses a loose-leafed herbarium containing 360 dried plant specimens, of which the provenance, age and maker were until recently unknown. By studying the plant specimens, paper, decorations and labels, an image was conveyed of an early 18th century herbarium that matched the description of a herbarium from the legacy of Jakob Ligtvoet, who was gardener in the Leiden Hortus botanicus from 1703 till his death in 1752. This herbarium is one of the oldest garden herbaria of its ki… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Their conclusion that only the individual specimens in Leiden can be linked to him with certainty is substantiated and further developed in this article. Recent research on two anonymous book herbaria that are also kept at Naturalis, the Zierikzee and the d'Oignies herbarium (in total 1116 plant specimens) led to the conclusion concluded that based on the species, their descriptions, pre-Linnaean names, decorations used, and the mention of corresponding herbaria in contemporary auction catalogues, these herbaria came from a botanical garden in or near Leiden in the first half of the 18th century (Offerhaus et al 2021;Offerhaus et al 2022).…”
Section: Commented [G11]mentioning
confidence: 99%
“…Their conclusion that only the individual specimens in Leiden can be linked to him with certainty is substantiated and further developed in this article. Recent research on two anonymous book herbaria that are also kept at Naturalis, the Zierikzee and the d'Oignies herbarium (in total 1116 plant specimens) led to the conclusion concluded that based on the species, their descriptions, pre-Linnaean names, decorations used, and the mention of corresponding herbaria in contemporary auction catalogues, these herbaria came from a botanical garden in or near Leiden in the first half of the 18th century (Offerhaus et al 2021;Offerhaus et al 2022).…”
Section: Commented [G11]mentioning
confidence: 99%
“…They can provide examples of pre-Linnaean nomenclature and systematics (Spalik, 2014;Pulvirenti & al., 2015;Costa & al., 2018Costa & al., , 2020Bertin & al., 2019), give indications on the uses of plants in the past (Van Andel & Barth, 2018) and provide evidence for the historical occurrence of species in a certain area (Santos-Guerra & al., 2011;Pulvirenti & al., 2017;Stefanaki & al., 2018). Furthermore, these collections of dried plants can provide indications about international relations and communication among scientists at the time of their production (Thijsse, 2016;Offerhaus & al., 2020). They are a part of the cultural heritage of the places where their plants were collected, and as such should be made accessible to the people of these regions (Van Andel, 2017).…”
Section: Introductionmentioning
confidence: 99%